Empowering employee innovation: a closer look at employees’ perceptions - Junttila, Juha (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Empowering employee innovation is on a focal point in today’s competitive business environment, as companies must be able to harness the creative equity of all of their organizational members in order to outperform competitors and increase market share. The existing literature argues that empowerment has a positive effect on employee innovation, yet it does not comprehensively explain how and why it is so. Due to these reasons this paper confronts the vaguely defined concept of empowerment by examining the theory via qualitative means in a manner of giving voice to the employees regarding their perceptions of empowerment and its relation to innovation. This study was carried out as an interpretive qualitative research to bring contrast to the previous empowerment studies that have been done quantitatively. The material was gathered by interviewing seven highly educated professionals who held no prior management experience by using semi-structured interview-method. The analysis method used was content analysis. The transcriptions were ultimately coded into aggregate dimensions that merged the acquired data and existing literature into insights, which both complement and challenge the existing empowerment theory. The results indicate that employees perceive the feeling of empowerment to be something intangible that variates continuously in time, and it can take variating influence from the surrounding work-environment depending of the individual employee. To manage empowerment structural- and psychological empowerment should be treated as interrelated constructs, where an empowering action eventually leads to various positive consequences via affecting employees’ four cognitions of psychological empowerment. In-depth information was acquired from antecedents of empowerment such as trust, empowering leadership, job characteristics and rewards. Further, the cognitions of self-determination and competence were identified to be most directly related to employee innovation. Thus, to enhance employee innovation via empowerment in a more direct way instead of focusing on actions that stimulate all of the four cognitions, the aim should be in key antecedents such as stimulating job characteristics and enabling immediate supervisor. Overall the employees’ perceptions emphasize that empowerment is not as black and white concept as literature makes it seem. To empower employee innovation an organization should aim the attention at the particular anteceding factors that are firmly knit to both employees’ everyday work-environment and the process of empowerment. Through these factors employees’ cognitions of self-determination and competence should be induced in a manner that they feel to be able to both think and act in a creative manner. The discoveries of this thesis added meaningful insights on top of the existing literature and provided a bridge into empowering employee innovation.